IKLIM KOMUNIKASI ORGANISASI DAN SEMANGAT KERJA PARA PERSONIL POLRI DI POLWIL SURAKARTA - Hastasari, Chatia (KOMUNITAS, 2015)
POLRI hasÂ  hierarchyÂ  organizationÂ  same withÂ  otherÂ  militaryÂ  institution. The occupationÂ  placementÂ  basedÂ  onÂ  levelÂ  ofÂ  promotion,Â  higherÂ  positionÂ  ofÂ  the POLRIâs promotion increase their occupation and their welfare. However, the higher level of lobby to the leader will determine the occupation, because not all occupation in police can increase the welfare of their personnel. This is the cause of polemic in police institution. The purposeof this research is to know the significant relation between organizational communication condition and working spirit of the POLRIâs personnel in POLWIL Surakarta and to know the significant relation between social economy status and the organizational communicationÂ  conditionÂ  andÂ  workingÂ  spiritÂ  ofÂ  theÂ  PolriâsÂ  personnelÂ  in POLWIL Surakarta. The type of this research is explanatory research thet will explainÂ  theÂ  causalÂ  relationÂ  betweenÂ  itsÂ  variableÂ  throughÂ  hypothesis examination.Â  TheÂ  researchÂ  usedÂ  surveyÂ  methodÂ  thatÂ  takeÂ  sampleÂ  from population and uesd questioner as the primary dataÂ  collector. The research take 76 sample use Yamane formula. There are 3 variables where the relation betweenÂ  independentÂ  variableÂ  (organzationalÂ  communication condition)Â  and dependentÂ  variableÂ  (workingÂ  spirit)Â  willÂ  beÂ  presentedÂ  byÂ  thirdÂ  variableÂ  that will be controled its effect (social economy status), so the writer used Kendall partial correlation coefficient. Based on the wholedata analysis result, it can beÂ  concludedÂ  thatÂ  amongÂ  theÂ  threeÂ  variablesÂ  namely, organzational communicationÂ  conditionÂ  (X),Â  workingÂ  spiritÂ  (Y)Â  and socialÂ  economyÂ  status (Z), the result is 0,752. the early value of Txy was 0, 765 and after the effect was controlled by social economy status (Z) becomes0, 752. so, it decrease about 0, 013. it means that social economy status is not the particular things thatÂ  effectÂ  theÂ  communicationÂ  conditionÂ  andÂ  working spiritÂ  ownedÂ  byÂ  the personnel of POLRI in POLWIL Surakarta.